Analysis of the effects of scanning trajectory parameters on minute-scale lidar forecasting. Issue 2 (1st May 2022) - Ortensi, M; Theuer, F; Kühn, M
Abstract: The definition of the lidar scan parameters for a measurement campaign can be complex and unsure due to the distinct effects that they cause on the lidar output. In order to study those effects on minute-scale lidar forecasting, we simulated several lidar trajectories in a large eddy simulation wind field. We analysed the effects of changes in range gate spacing, and angular and temporal resolution on the accuracy of wind field reconstruction and on the forecast skill of 5 minute ahead deterministic wind speed forecasts. We found that the range gate spacing has no influence on forecast skill. Furthermore, we discussed the forecasting improvement caused by the increase in angular resolution, and its unexpected worsening caused by the reduction in temporal resolution. We concluded that high values for range gate spacing do not reduce the forecast skill, and that the effects of changes in angular and temporal resolution on forecast accuracy can differ among the wind turbines.